Mobile investment and traffic per capita tend to increase with license duration - Francois Jeanjean; Marc Lebourges; Julienne Liang (International Telecommunications Society (ITS), 2018)
Using source WCIS (World Cellular Information Service) for the tangible investments of mobile operators and mobile spectrum licenses, we are able to build a database matching the level of investment per capita with average license duration for 14 countries (representing more than 75% of the number of mobile subscribers of the EEA area) during 15 years. The statistical analysis of the data base proves a strong positive correlation between license average duration and tangible investment per capita. More precisely, we observe an increase of 5.36 e in average investment per capita per year for each additional year of license duration. This feature also holds at operator level. Using Data traffic from Telecom Market Matrix at country level, we also observe that each additional year of license duration corresponds to about 10% additional yearly growth of data traffic.
Keywords: 330